Sentiment analysis of hotel reviews in Malaysia - Withanage, Madusha Sandamali (2018)
Hotel industry in Malaysia can be described as monopolistic competitive market structure where many competitors exist and market share is obtained through product/ service differentiation. The aim of this study was to determine the sentiment drivers affecting customers’ choice of a hotel and provide recommendations to hotel owners about customer insights and preferences for each sentiment driver. The Latter part of the study focused on the relationships among sentiment drivers, behaviour intention (online review ratings) and usage behaviour (customer sentiment) of hotel customers in Malaysia.